ChemInform Abstract: Na2TeS3, Na2TeSe3‐mP24, and Na2TeSe3‐mC48: Crystal Structures and Optical and Electrical Properties of Sodium Chalcogenidotellurates(IV). Issue 7 (January 2016) - Pompe, Constantin; Preitschaft, Christian; Weihrich, Richard; Pfitzner, Arno
Abstract: Pure samples of Na2 TeQ3 (Q: S, Se) are prepared by reactions of stoichiometric amounts of the elements (graphite crucibles, 670—1170 K, 3 h—10 d) and characterized by single crystal XRD, UV/VIS, Raman, and impedance spectroscopy, and DFT calculations.